2018
DOI: 10.1080/00103624.2018.1474909
|View full text |Cite
|
Sign up to set email alerts
|

Sufficiency ranges and crop nutrient removals for peppermint (Mentha X piperita L.) established from field and pot fertilizer experiments

Abstract: Peppermint is an important aromatic and medicinal plant used across the world in pharmaceutical, cosmetic and food industries. However, there is a lack of agronomic research on this crop which hinders the implementation of best agricultural practice at farm level. Plant analysis, for instance, cannot be used as a tool to implement a suitable fertilizer recommendation program, since sufficiency ranges and crop nutrient removals have not yet been established. Thus, the main objectives of the present work were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…N is a limiting factor for plant growth, particularly in potted plants with reduced space for root expansion (Ferreira et al, 2020;Rodrigues et al, 2018), and can be taken up to luxury consumption levels when available in the soil (Havlin et al, 2014). Thus, the lower N concentration in the control and K-silicate treatments was mainly the result of a dilution effect, which occurs due to the increase in plant biomass for the same amount of N available in the growing medium (Arrobas, Ferreira, et al, 2018b;Jarrel & Beverly, 1981).…”
Section: Discussionmentioning
confidence: 95%
“…N is a limiting factor for plant growth, particularly in potted plants with reduced space for root expansion (Ferreira et al, 2020;Rodrigues et al, 2018), and can be taken up to luxury consumption levels when available in the soil (Havlin et al, 2014). Thus, the lower N concentration in the control and K-silicate treatments was mainly the result of a dilution effect, which occurs due to the increase in plant biomass for the same amount of N available in the growing medium (Arrobas, Ferreira, et al, 2018b;Jarrel & Beverly, 1981).…”
Section: Discussionmentioning
confidence: 95%
“…This thesis is supported by the increase in organic C and Kjeldahl N in the soil, revealing that part of the applied N is still in organic form. The increase in the production of grapes and, above all, the increase in weeds' dry matter yield gave rise to a dilution effect, which normally contributes to the reduction of the concentration of nutrients in the tissues (Arrobas et al, 2018;Jarrell & Beverly, 1981). Many other inefficiencies of N use may have contributed to the result.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the usual soil organic matter content in perennial crops in the region is low (Arrobas et al, 2018;Rodrigues & Arrobas, 2020;Rodrigues et al, 2015), and given also the scarcity of farmyard manure, the possibility of using this resource is very attractive for some farmers. In this study, results are reported of the effect of the application of the compost 'Ferti Trás-os-Montes' in an experimental vineyard at the rate of 20 t ha −1 over three consecutive years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of almost all the nutrients analysed varied significantly with the year, irrespective of plant tissue and sampling date. This great dynamic in tissue nutrient concentrations depends on diverse factors; one of the most relevant of these is the dilution/concentration effect related to nutrient uptake and carbon assimilation, and plant growth [34,40], which does not justify further development here. SPAD readings and chlorophyll fluorescence and OJIP transient variables presented inconclusive results, they too are probably related to the concentration of nutrients in the tissues and dilution/concentration effects [37].…”
Section: Discussionmentioning
confidence: 99%